The deaf dialogue between CJEU and Immigration Law: from the United Kingdom to the Spanish case - Marín Consarnau, Diana (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
The aim of this report is to study the difficulties in practice to link the CJEU criteria related to the art. 20 and 21 TFEU with the national Immigration Law in the field of derived rights of residence for the family members of the Union citizens, specially in those regulations that promote the reverse discrimination with direct effects, as in the United Kingdom, and even indirectly, as it results in the Spanish case.